Quantum stochastic processes: boson and fermion Brownian motion - Kobryn, A.E.; Hayashi, T.; Arimitsu, T. (Condensed Matter Physics, 2003)
Dynamics of quantum systems which are stochastically perturbed by linear
coupling to the reservoir can be studied in terms of quantum stochastic
differential equations (for example, quantum stochastic Liouville equation
and quantum Langevin equation). In order to work it out one needs to define the quantum Brownian motion. As far as only its boson version has
been known until recently, in the present paper we present the definition
which makes it possible to consider the fermion Brownian motion as well. Динаміка квантових систем, що зазнають збурення через лінійну
взаємодію із термостатом стохастично, може бути описана за допомогою квантових стохастичних диференціальних рівнянь (наприклад, квантового стохастичного рівняння Ліувіля, або квантового
рівняння Ланжевена). Для цього необхідно дати означення квантового броунівського руху. Оскільки донедавна воно було наведене
лише для бозонних систем, у даній роботі показується як таке означення можна ввести у випадку ферміонних систем.